Resolution of chiral compounds by crystallization - Ching, Chi Bun. (2010)
Objectives of this project are: (1) Understanding of the factors that control the formation of enantiomerically pure and racemic crystals. (2) Development of a reliable racemic species characterization method. (3) Development and optimization of chiral crystallization processes for different racemic species of commercial interest. In this project, a systematic approach has been developed and applied to preferential crystallization of chiral molecules by integration of system thermodynamics, crystallization kinetics, optimal operation and in-situ monitoring. Three types of racemate crystals were identified with thermal analysis and structural characterizations. Their metastable zone widths in solution were found as an additional characteristic to identify racemic species. Primary nucleation order variations with enantiomeric excess suggested there exists a critical supersaturation beyond which the nucleation of opposite isomer could occur. A dynamic method was developed and used to measure the crystallization kinetics of several systems. With combination of thermodynamics and crystallization kinetics, a detailed mathematical modeling was established to predict the operation strategy. The product's optical purity, crystal morphology and in-situ observations, all suggested that the critical supersaturation control was essential and the systematic approach was successful and applicable for preferential crystallization of chiral compounds.